The mitochondrial genome of a wild edible mushroom, Russula rosea - Fei Yu; Junfeng Liang (Mitochondrial DNA. Part B. Resources, 2022)
Russula rosea is a common wild edible ectomycorrhizal fungus, which is widely distributed all over the world. We assembled the complete mitochondrial genome of R. rosea with the total length was 54177 bp and the GC content of 22.34%. It contains a total of 57 genes, including 14 standard protein-coding genes, one conserved ribosomal protein S3 gene (rps3), two rRNA genes, 24 tRNA genes, 15 free-standing open reading frames (ORFs) and one DNA polymerase gene (dpo). Mitochondrial genome found a close evolutionary relationship between Russula rosea and Russula lepida, which was helpful to study the genetic evolutionary relationship of edible fungi.